SEPSIS СAUSED BY HAEMOPHILUS INFLUENZA - A. L. Rossina; S. B. Chuelov; A. A. Korsunskiy; O. A. Kaschenko; M. V. Popova; O. Y. Brunova; T. S. Trifonova; E. S. Tarasova; M. K. Astamirov; S. А. Basharin; A. V. Stupina; I. V. Girutskaya; et al. (LLC "Diagnostics and Vaccines", 2018)
The article provides clinical examples of hemophilic sepsis developed in non-vaccinated children with immunodeficiency conditions resulted in death.